MOTIVATIONAL MANAGEMENT OF DIRECTORS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS IN WORKING WITH PERSONNEL (Neo Scientific Peer Reviewed Journal, 2025)
This article analyzes the mechanisms for effectively organizing motivational management in the process of working with personnel by directors of preschool educational organizations. The study highlights the leadership competencies of the leader in managing the pedagogical team, the psychological and organizational factors of identifying the needs and professional interests of employees, and their motivation. The application of motivational management strategies by the director of a preschool educational organization results in the formation of a healthy working environment in the team, an increase in the professional activity of employees and their responsibility for the quality educational process.